2016
DOI: 10.1186/s12870-016-0800-x
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress tolerance strategies revealed by RNA-Seq in two sorghum genotypes with contrasting WUE

Abstract: BackgroundDrought stress is the major environmental stress that affects plant growth and productivity. It triggers a wide range of responses detectable at molecular, biochemical and physiological levels. At the molecular level the response to drought stress results in the differential expression of several metabolic pathways. For this reason, exploring the subtle differences in gene expression of drought sensitive and drought tolerant genotypes enables the identification of drought-related genes that could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
167
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 105 publications
(95 reference statements)
19
167
2
2
Order By: Relevance
“…More number of unigenes was either up or down-regulated in DS than DT indicating sensitive genotypes were relatively hyper-responsive to stress and or easily disturbed by drought stress at molecular level. Our findings supports the reports of Yates et al (2014) and Fracasso et al (2016) who observed drought-sensitive genotypes of other plants (Clover and Sorghum) were found to be hyper-responsive to drought stress in comparison to their respective tolerant genotypes. This may be an indicative of absence of some transient and or primary layer of stress avoidance mechanism in sensitive cultivars to mitigate drought effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More number of unigenes was either up or down-regulated in DS than DT indicating sensitive genotypes were relatively hyper-responsive to stress and or easily disturbed by drought stress at molecular level. Our findings supports the reports of Yates et al (2014) and Fracasso et al (2016) who observed drought-sensitive genotypes of other plants (Clover and Sorghum) were found to be hyper-responsive to drought stress in comparison to their respective tolerant genotypes. This may be an indicative of absence of some transient and or primary layer of stress avoidance mechanism in sensitive cultivars to mitigate drought effects.…”
Section: Discussionsupporting
confidence: 93%
“…However, greater extent of reduction of TFs was noted in DT is not clear and information such as identification of precise target genes and regulatory pathways and their consequences may be essential to further understanding. Very recently Fracasso et al (2016) too found that TFs were largely reduced in tolerant sorghum genotypes than sensitive genotypes under drought stress conditions. Around 46 TF families including MYB, NAC, WRKY, bHLH, bZIP, ERF, and HSFs were differentially expressed in banana cultivars to drought stress ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-canopy WUE i values were different from WUE i calculated at leaf level in Fracasso et al (2016b). While at leaf level WUE i of WS plants decreased according to decreasing FTSW, at whole-canopy level WUE i of WS plants increased with the decreasing FTSW.…”
Section: Discussioncontrasting
confidence: 61%
“…We observed a lower WUE i for IL 4‐1 under WD conditions compared with the other lines under study (Table ), whereas WUE i in IL 11‐3 was higher under WD compared with WW conditions (Table ). This increase in WUE i has been reported in drought‐tolerant varieties in several crops (Guha et al ., ; Fracasso et al ., ; Liu et al ., ), although it might not always have a positive effect on fruit yield. Interestingly, none of the ILs under study were considered before for WUE improvement as they showed no differences in δ 13 C compared with M82 (Xu et al ., ), in agreement with our results, so this epidermis‐based analysis provides an alternative path for increased WUE.…”
Section: Discussionmentioning
confidence: 99%